2006
DOI: 10.1243/09576509jpe154
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional quasi-unsteady flow simulation in a centrifugal pump: Comparison with experimental results

Abstract: This work aims at assessing the velocity field, pressure, and radial thrust distribution inside a centrifugal pump (ENSIVAL-MORET MP 250.200.400 pump, diameter ¼ 408 mm, five blades, specific speed ¼ 32) at various flowrates. A three-dimensional flow simulation is first presented for the isolated impeller. A three-dimensional quasi-unsteady flow simulation of the impeller -volute assembly is then performed for several impeller blades and volute tongue relative positions. The computed pressure fields enable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Satisfactory and good agreements between the numerical and experimental results have been obtained. Asuaje et al [13] performed a quasi-unsteady flow simulation for a centrifugal pump by using the same software. The numerical and test results of the pressure fluctuation at impeller exit are globally satisfactory.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Satisfactory and good agreements between the numerical and experimental results have been obtained. Asuaje et al [13] performed a quasi-unsteady flow simulation for a centrifugal pump by using the same software. The numerical and test results of the pressure fluctuation at impeller exit are globally satisfactory.…”
Section: Numerical Modelmentioning
confidence: 99%
“…1. The research efforts on centrifugal pumps and compressors by Zhang and Lakshminarayana [16], Asuaje et al [17], and Kaewnai et al [18] all showed that the standard κ-ε model provided results with acceptable accuracy. 2.…”
Section: Numerical Modelmentioning
confidence: 99%
“…The comparisons, between the numerical results and the experimental data, indicated that the standard κ-ε model, algebraic eddy viscosity model, and the algebraic Reynolds stress model showed the same level of agreement in the simulation of the pressure-driven secondary flows. Asuaje et al [17] experimentally and numerically studied the flow in a pump, which has a semi-open centrifugal impeller and a squirrel fluid collector. Predictions with various turbulence models were compared to the experimental data.…”
Section: Introductionmentioning
confidence: 99%